Research on Physical Layer Security Performance of Hybrid RF/FSO System Based on RIS Assistance under FSO Eavesdropping Environment - Sun Qingjie; Dexian Yan; Yi Wang (IEEE Photonics Journal, 2024)
This paper proposes ahybrid RF/FSO system based on RIS reflection to interfere with eavesdroppers in FSO eavesdropping scenarios, and analyzes and optimizes the physical layer security performance of this communication system. In this work, the RF link experiences Nakagama-m distribution, there is a single-antenna eavesdropper E1 trying to eavesdrop on the RF link information, and the RIS reflection friendly interference signal is used to interfere with the RF link. The FSO link follows the Málaga (M) distribution. There is a single-antenna passive eavesdropper with optical eavesdropping equipment near the destination node to capture the optical signal sent by the relay and eavesdrop on the information. Based on the above communication model, we derive the Strict Positive Secrecy Capacity (SPSC) and Secure Outage Probability (SOP) under double eavesdropping, and use the Monte Carlo method to verify the correctness of the expressions. The impact of various parameters in the system on safety performance was analyzed. The results showed that the interference signal-to-noise ratio, time switching factor and energy conversion efficiency of the wireless power supply jammer, the increase in the number of RIS reflective elements, good weather conditions and better detection methods, etc. All influencing factors can improve physical layer security performance, which also lays a theoretical foundation for the application of hybrid RF/FSO systems where eavesdropping exists in both RF links and FSO links.